(untitled) (Third Sector Social Economic Review, 2025)
In today’s conditions, in addition to online purchasing being common, information can also be sought before purchasing. This behavior of consumers who turn to physical channels and make purchases after searching for information is defined as webrooming in the literature. It is very important to determine the underlying causes of these behaviors. Since the behavior in question is a transition from online to physical, it is important to determine whether this is related to trust in the channel or not in terms of understanding the issue. Based on this idea, this study aims to determine the effect of source risk, one of the online perceived risk dimensions, on webrooming behavior in the tour purchasing behavior of individuals who live in Istanbul and have purchased a tour from a physical tour agency in the last year. The survey prepared for this purpose was applied to 403 individuals on a voluntary basis. As a result of the Linear Factor Analysis conducted to determine whether the scales were collected under a single dimension in the research, it was determined that both scales provided the 3-item single-factor dimension in their original structure. When Cronbach’s Alpha, CR and AVE values were evaluated to determine the reliability of both scales, it was determined that both scales were valid and reliable scales. Structural Equation Modeling was conducted to determine the effect of participants’ source risk perceptions on their webrooming behavior. As a result of the analysis, it was determined that source risk, one of the risk factors perceived online, had a positive effect on webrooming behavior.